Composing and realising a game-like performance for disklavier and electronics - Kallionpää, Maria; Greenhalgh, Chris; Hazzard, Adrian; Weigl, David M.; Page, Kevin R.; Benford, Steve (2017)
“Climb!” is a musical composition that combines the ideas of a classical virtuoso piece and a computer game. We present a case study of the composition process and realization of “Climb!”, written for Disklavier and a digital interactive engine, which was co-developed together with the musical score. Specifically, the engine combines a system for recognising and responding to musical trigger phrases along with a dynamic digital score renderer. This tool chain allows for the composer’s original scoring to include notational elements such as trigger phrases to be automatically extracted to auto-configure the engine for live performance. We reflect holistically on the development process to date and highlight the emerging challenges and opportunities. For example, this includes the potential for further developing the workflow around the scoring process and the ways in which support for musical triggers has shaped the compositional approach.